2022
DOI: 10.1097/jcma.0000000000000767
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the blood urea nitrogen to creatinine ratio in in-hospital cardiac arrest after targeted temperature management

Abstract: Background: Targeted temperature management (TTM) has been reported to improve outcomes in in-hospital cardiac arrest (IHCA) patients but little has been investigated into the relationship between prognoses and the blood urea nitrogen to creatinine ratio (BCR). Methods: A retrospective analysis of data from IHCA survivors treated with TTM between 2011 and 2018 was conducted based on the Research Patient Database Registry of the Partners HealthCare system in Boston. Serum laboratory data were measured during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…10 Additionally, the authors found a cutoff value of 16.7 for a post-TTM BCR with a sensitivity of 61.9% and a specificity of 70.0% to predict poor neurological outcome at discharge among IHCA patients. 10 The current article is interesting and worthy of further discussion.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…10 Additionally, the authors found a cutoff value of 16.7 for a post-TTM BCR with a sensitivity of 61.9% and a specificity of 70.0% to predict poor neurological outcome at discharge among IHCA patients. 10 The current article is interesting and worthy of further discussion.…”
mentioning
confidence: 92%
“…10 Similarly, after ischemic stroke, lower BCR was associated with better neurological function. 10 All suggest that a higher BCR (poor renal function or severity of AKI) may be associated with worse outcomes, especially for patients with a poor neurological prognosis. We agree with the authors' opinion; however, some concerns should be announced.…”
mentioning
confidence: 96%
See 3 more Smart Citations